Online Prostitution Amidst the Rapid Technological Advances: Legal and Social Aspects - Permata, Verania Hedi (Universitas Negeri Semarang, 2021)
Today almost everyone is using the internet, because from the internet we can get all the information easily and quickly. but not everyone knows the dangers of using the internet. because it is not uncommon also someone to commit crimes through the internet (cyber crime). cyber crime is the negative side of technological advances for all areas of modern life that exist today. one of the crimes that can occur through internet access is online prostitution. The online prostitution activity is a negative impact of social media abuse. One effort that can be used to cope with online prostitution activity that occurs is with the approach of criminal law policy through criminal sanctions as a concrete form of criminal responsibility to perpetrators of online prostitution. The disclosure of online prostitution cases proves that social media is a powerful tool for the promotion of prostitution. Such prostitution activity is the effect of unlimited use of online social media. In the absence of a national regulation that regulates this matter, online prostitution users will feel secure and liberal in purchasing services for their own satisfaction, while in fact it is contrary to legal norms in society.